REVITALISASI PRINSIP SYURA DALAM DEMOKRASI KONSTITUSIONAL INDONESIA: KAJIAN INTEGRATIF ANTARA FIQIH SIYASAH DAN HUKUM TATA NEGARA - Arsanda Rizkia Fadilah; Alifah Khoirunisa; Delvin Agliana; Nur Rahmah (Universitas Khairun, 2025)
Ijtihad is an essential means in the renewal of Islamic law and has been the subject of intense debate. In the modern context, ijtihad is used to address the challenges and social changes in society. From the time of Prophet Adam to Prophet Muhammad (peace be upon him), Allah sent messengers to guide humanity towards the truth. When people encounter issues not explicitly addressed in the Quran and Sunnah, Allah grants the freedom to use reason (ijtihad) to solve those problems, provided that the principles of the Quran and Sunnah, as the primary sources of law, are followed. The need for ijtihad has continuously increased with the growing number of issues faced by Muslims after the death of the Prophet, especially as the Islamic territories expanded and issues became more complex. This paper will discuss the dynamics of ijtihad in the renewal of modern Islamic law and its challenges, using a juridical-historical approach. This research is a descriptive qualitative library research, utilizing various literary sources to analyze and explain the role of ijtihad in the renewal of modern Islamic law. The results of the study indicate that ijtihad plays a crucial role in the renewal of Islamic law, allowing it to remain relevant and responsive to the changing times, despite facing various challenges.